Diet and Dermatology: The Role of a Whole-food, Plant-based Diet in Preventing and Reversing Skin Aging—A Review - Solway, Jason (J Clin Aesthet Dermatol, 2020)
BACKGROUND: Previous studies have demonstrated that a whole-food, plant-based (WFPB) diet can aid in the prevention, and in some cases reversal, of some of the leading chronic diseases in the United States. The medical literature on the relationship between diet and disease is steadily growing. Over the last decade, the possible connection between diet and many dermatological conditions has been studied, including skin aging. OBJECTIVE: As patients are increasingly seeking dietary advice from their dermatologist related to preventing and reversing the aging of skin, dermatologists need an evidence-based approach to tackle this challenging topic. This review focuses on dietary factors that contribute to telomere length, a marker for cellular aging. Although various factors contribute to accelerating telomere shortening, this review focuses on dietary factors that contribute to telomere length, specifically gerontotoxins and antioxidants. These can be measured in the blood, making them biomarkers of accelerated cellular skin aging. Included in this discussion is an evidence-based approach to increase the amount of antioxidants and decrease the amount of gerontotoxins in the diet, resulting in healthier skin. METHODS: A comprehensive MEDLINE (PubMed) literature review search was performed. Keywords used included: WFPB, telomerase, coronary artery disease, cellular aging, cigarette smoke, photoaging, telomeres, antioxidants, gerontotoxins, intrinsic cutaneous aging, extrinsic cutaneous aging, advanced glycation end products (AGEs), vitamin E, vitamin C, vitamin E, CoQ10, polyphenols, chlorophyll, zeaxanthin, polyunsaturated fatty acids, eicosapentaenoic acid, docosahexaenoic acid, alpha-linolenic acid, and monounsaturated fatty acids. Inclusion criteria included the above stated keywords and access to full text. RESULTS: A WFPB diet maximizes the antioxidant potential within our cells by providing essential vitamins, including vitamins A, C, and E. It also helps to eliminate harmful carcinogens and gerontotoxins within our bloodstream and has been shown to lengthen telomeres, which prevents cellular damage. CONCLUSION: Evidence obtained within this literature review supports a WFPB diet for preventing skin aging. .